Demografi Kumbang Elaeidobius kamerunicus Faust (Coleoptera: Curculionidae) sebagai Serangga Polinator pada Tanaman Kelapa Sawit [The Demographic of Elaeidobius kamerunicus Faust Beetle (Coleoptera: Curculionidae) as Insect Pollinators on Oil Palm Plant] - Novalisa Lumentut; Meldy L.A. Hosang (Buletin Palma, 2016)
The role of pollinator beetles E. kamerunicus in oil palm plantations needed for pollination and increase fruit formation. E. kamerunicus beetle pollen can move well on oil palm. This research aims to study the demographic E. kamerunicus statistics to predict the rate of growth. This study used male flower oil palm as a breeding and insect pollinators E. kamerunicus obtained and in the collection of the field in the oil palm plantations in the district Wood tides of Province West Sulawesi and in Pamona district, Central Sulawesi and the Laboratory of Entomology Indonesian Palmae Research Institute from January to October 2015. Data were analyzed by analysis of variance and analysis of demographic statistics includes the net reproductive rate, generation time, intrinsic growth rate. The results show that the value of demographic E. kamerunicus is Ro= 4.88, rm= 0.084 and T= 19 days. Ro value indicates multiple populations per generation E. kamerunicus on oil palm male flowers 4.88-fold for 19 days. Rated E. kamerunicus Ro> 1, meaning that the population of E. kamerunicus will increase. Ro and rm valueand shows that the male flower oil palm is suitable for the development of host E. kamerunicus evidenced by the reproduction rate of the population of insect pollinators multiples of this very quickly with the average time needed by one generation is 19 days to increase its population. With the increasing population of insect pollinators E. kamerunicus in oil palm plantations will have an impact on the success of oil palm fruit pollination for fruit formation, thereby increasing the productivity of oil palm. The results of the research can be used to determine the rate of population E. kamerunicus per generation in palm oil plantations that role as insect pollinators and pollination success of oil could have implications for improved productivity of oil palm in Indonesia.ABSTRAKPeranan kumbang polinator E. kamerunicus di pertanaman sawit diperlukan untukpenyerbukan guna meningkatkan pembentukan buah karena kumbang E. kamerunicus dapat memindahkan serbuk sari pada sawit. Penelitian ini bertujuan mempelajari demografi statistik E. kamerunicus untuk memprediksi laju pertumbuhannya pada bunga jantan kelapa sawit. Penelitian dilaksanakan di Laboratorium Entomologi Balai Penelitian Tanaman Palma mulai bulan Januari - Oktober 2015. Pengambilan kumang E. kamerunicus pada pertanaman kelapa sawit di Kabupaten Pasang Kayu Provinsi Sulawesi Barat dan di Kabupaten Pamona Provinsi Sulawesi Tengah. Data dianalisis dengan analisis ragam dan analisis statistik demografi meliputi laju reproduksi bersih, waktu generasi, dan laju pertumbuhan intrinsik. Hasil penelitian menunjukkan nilai demografi E. kamerunicus adalah Ro= 4,88,  rm = 0,084 dan T= 19 hari.Nilai Ro menunjukkan kelipatan populasi E. kamerunicus per generasi pada bunga jantan kelapa sawit adalah 4,88 kali lipat selama 19 hari. Nilai Ro E. kamerunicus >1, artinya populasi E. kamerunicus akan meningkat. Nilai Ro dan rm menunjukkan bahwa bunga jantan sawit merupakan inang yang cocok untuk perkembangan E. kamerunicus dibuktikan dengan besarnya laju kelipatan reproduksi populasi serangga polinator ini dengan sangat cepat dengan waktu rata-rata yang dibutuhkan oleh satu generasi adalah 19 hari untuk meningkatkan populasinya. Dengan meningkatkatnya populasi serangga polinator          E. kamerunicus di perkebunan sawit akan berdampak pada keberhasilan penyerbukan buah sawit untuk pembentukan buah sehingga dapat meningkatkan produktivitas sawit. Hasil penelitian dapat digunakan untuk mengetahui laju pertambahan populasi E. kamerunicus per satu generasi di perkebunan sawit sehingga peranannya sebagai serangga polinator dan keberhasilan penyerbukan sawit dapat berdampak bagi peningkatan produktivitas kelapa sawit di Indonesia.